Use of α,ω-Dichloroketimine Building Blocks for the Construction of 1-Azabicyclo[3.1.0]hexanes, Piperidines, Pyridines, Pyrroles, and Tetrahydroindoles - Piens, Nicola; Aelterman, Wim; D’hooghe, Matthias; De Kimpe, Norbert (Synlett, 2017)
A variety of different N-[2-chloro-4-(chloromethyl)pent-4-enylidene]amines and N-(2,6-dichlorohex-4-enylidene)amines was prepared for the first time, and their reactivity as eligible building blocks for the synthesis of biologically relevant nitrogen-containing heterocyclic compounds was studied. In this way, a convenient entry into functionalized 1-azabicyclo[3.1.0]hexanes, piperidines, pyridines, pyrroles, and tetrahydroindoles was developed, pointing to the broad synthetic flexibility of these dichlorinated imine substrates.
Keywords: α,ω-dichloroketimines; 1-azabicyclo[3.1.0]hexanes; piperidines; pyridines; pyrroles; tetrahydroindoles